Wind-induced fatigue assessment of welded connections in steel tall buildings using the theory of critical distances. Issue 8 (2nd July 2020) - Fang, Zhao; Li, Aiqun; Ding, Youliang; Li, Wanrun
Abstract: At present wind-induced fatigue assessment of welded engineering structures is mainly based on nominal stress or structural stress concepts, which cannot fully consider the effect of stress concentration and stress gradient around notches. In order to address this problem, the theory of critical distances (TCD) is applied to fatigue assessment of a welded beam-to-column connection in a steel tall building, through establishment of a multi-scale finite element model. The convergence characteristic of the TCD is also verified and results are compared to those obtained by the equivalent structural stress method, the hot-spot stress method and the notch stress approach. The results show that the TCD is reliable in wind-induced fatigue assessment and convergence can be achieved. Reliable results can be obtained when the mesh size in 3D solid elements around notches is smaller than the critical distance value. The TCD tends to be more conservative than the other methods in high stress gradient areas due to the consideration of stress gradient near notches.